PENERAPAN KONSEP TASAWUF TENTANG SABAR DAN IKHLAS DI LINGKUNGAN PONDOK PESANTREN PUSAT PUTRI ZAINUL HASAN GENGGONG - Mawaddah, Mawaddah; Muzakki, Ahmad; Nikmah, Shofiatun (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to describe the application of Sufi concepts of sabr (patience) and ikhlas (sincerity) in the daily lives of students (santri) in an Islamic boarding school (pondok pesantren) environment. Patience and sincerity are central values in Sufism that are believed to shape strong spiritual character and enhance mental resilience in facing life's challenges. This research employs a qualitative approach with a case study method conducted at a traditional Islamic boarding school in East Java. Data were collected through observations, in-depth interviews with caregivers, teachers, and students, as well as documentation of daily pesantren activities. The findings show that the values of patience and sincerity are instilled through spiritual guidance such as wirid (repetitive prayer), Sufi book studies, and a culture of simple living. These values are also reflected in students’ attitudes toward duties, rules, and social interactions within the pesantren. In conclusion, the implementation of the concepts of sabr and ikhlas not only strengthens students’ spiritual character but also fosters a harmonious and conducive atmosphere in pesantren life. The study recommends incorporating Sufi-based approaches as a foundation for character development in Islamic educational institutions.